Relationship Between Ivestors Sentiment Index with Frst and Second Market Indexes in Tehran Stock Exchange (TSE) - Fayyazi, Hadi; Maharlouei, Rasoul Goshtasbi (Ciência e Natura, 2015)
The process of being affected of the investors in decision making from their sentiment has been considered in many recent researches in the field of the financial assets pricing. Some authors suggest that shifts in investor sentiment may in some instances better explain short-term movement in asset prices than any other set of fundamental factors. The present study tries to investigate the relation between the investors sentiment index and First and Second Market Indexes in Tehran Stock Exchange Market. This paper, an index was used in order to measure the available data on sentiment of the investors in facing the risks in a 142-month period (2001 – 2014) in Tehran Stock Exchange. The used index can reveal and present the situation of the Iranian capital Market in terms of the Investors Sentiments. The results obtained from the present study reveal a positive and significant relation between the investors’ sentiment Index of the Tehran Exchange First and Second Market Indexes; and also by using from Granger Causality Test, it was revealed that there is a mutual causality relation between the investors’ sentiment Indexes of the TEFMIX and TESMIX.